2016
DOI: 10.1175/jcli-d-15-0337.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation on Summer Precipitation over the United States

Abstract: Irrigation’s effects on precipitation during an exceptionally dry summer (June–August 2012) in the United States were quantified by incorporating a novel dynamic irrigation scheme into the Weather Research and Forecasting (WRF) Model. The scheme is designed to represent a typical application strategy for farmlands across the conterminous United States (CONUS) and a satellite-derived irrigation map was incorporated into the WRF-Noah-Mosaic module to realistically trigger the irrigation. Results show that this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
104
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 77 publications
9
104
0
Order By: Relevance
“…For example, Pei et al (2016) used a potential evapotranspiration ratio to estimate June, July, and August irrigation usage from USGS yearly county-level estimates in order to validate irrigation amounts in the Weather Research and Forecasting model (WRF)-Noah mosaic coupled model. The study found good agreement between the amounts simulated and that of the modified observations at 30 km horizontal resolution.…”
Section: Evaluation Of Irrigation In Lsmsmentioning
confidence: 99%
“…For example, Pei et al (2016) used a potential evapotranspiration ratio to estimate June, July, and August irrigation usage from USGS yearly county-level estimates in order to validate irrigation amounts in the Weather Research and Forecasting model (WRF)-Noah mosaic coupled model. The study found good agreement between the amounts simulated and that of the modified observations at 30 km horizontal resolution.…”
Section: Evaluation Of Irrigation In Lsmsmentioning
confidence: 99%
“…This is particularly relevant in areas of high irrigation where modified soil moisture significantly impacts the regional hydroclimate through adjusted land-atmosphere interactions Snyder 2012a, 2012b;Jódar et al, 2010;Lo and Famiglietti, 2013;Rojstaczer 2001, 2002;Pei et al, 2016;Qian et al 2013). One major effect of increased soil moisture is on the Great Plains low-level jet (GPLLJ; Walters et al, 2014;Weaver and Nigam, 2011).…”
Section: Regional Climatementioning
confidence: 99%
“…Irrigation-induced changes in local precipitation are mostly tied to changes in large-scale moisture convergence, and thus to changes in precipitation elsewhere. Besides, local and downwind effects can occur simultaneously (Pei et al, 2016). Im and Eltahier (2014) even detected, in a simulation experiment, a constellation in which irrigation increased rainfall (by 100 %) and runoff (by 50 %) in the Niger River basin upstream from the irrigation location.…”
mentioning
confidence: 99%